Optimization of Crude Fish Oil Extraction Using Mechanical Screw Expeller Validated by Response Surface Methodology - Bako, Tanko; Umogbai, Victor Imolemhe; Garba , Anebi Joseph (Journal of Postharvest Technology, 2018)
Fish has been identified as a source of essential oil, but there is sparse literature on the effect of processing factors on the characteristics of oil extracted from any fish species. Optimization of oil extraction with the aid of expeller was achieved by applying response surface methodology. The variables were choke clearance (1–3 mm), screw clearance (1–3 mm) and screw speed (50–70 rpm), while the responses were oil yields. Data obtained were analyzed at P < 0.05. Choke clearance, screw clearance and screw speed conditions significantly influenced all the responses at P < 0.05. The optimum oil extraction condition was 1 mm choke clearance, 1mm screw clearance and 70 rpm screw speed, which gave 22.422 % oil yield.